Dexamethasone Down-Regulates the Expression of microRNA-155 in the Livers of Septic Mice - Wang, Zhong-hua; Liang, Yan-bing; Tang, Hao; Chen, Zhi-bin; Li, Zhen-yu; Hu, Xu-chu; Ma, Zhong-fu (PLOS ONE, 2013)
To investigate the expression of microRNA-155 (miRNA-155) in the livers of mice with lipopolysaccharide (LPS)-induced sepsis and to determine the role of dexamethasone (DXM) in the regulation of miRNA-155 expression, we pretreated mice with or without DXM prior to LPS exposure. Our study demonstrated that the expression of miRNA-155 and inflammatory factors increased in the liver tissues of mice with LPS-induced sepsis and that DXM down-regulated their expression in a dose-dependent manner. Moreover, DXM alone inhibited the expression of miRNA-155 to below the baseline level, but did not impact the expression of inflammatory factors, suggesting that the down-regulation of miRNA-155 by DXM may partially, but not completely, depend on the suppression of pro-inflammatory cytokines by DXM. Our data indicate that the overexpression of miRNA-155 in the livers of mice with LPS-induced sepsis may play an important role in the pathological processes of sepsis and that the down-regulation of miRNA-155 by DXM may be a novel mechanism regulating inflammation and immunity.